Linguistic Prejudice in Kurdish - Aziz, Aryan Sdiq; Hama Saeed, Rasti Ayub (Journal of Linguistics and Social Sciences, 2023)
Linguistic prejudice is a hidden message used by speakers of a language in daily conversations, either individually or in groups, through implicature and is fixated later as an idiom. Linguistic prejudice, an output of negative stereotypes and bountiful appearance in utterances, excludes others from goodness and virtues to show itself as excellent and perfect. Now, the Kurdish language is developing and enriching in the linguistic field. Its linguists and researchers always try to purify it from other languages' hegemony and effect to put it on the right track and make it stand firm before other languages, particularly those of neighboring nations. But, mainly for the sake of serving this noble purpose, they followed the same mistakes ways and policies of other languages. Therefore linguistic prejudice has been noticed in various aspects and fields. This research tries to show linguistic prejudice and its types. What do we mean by linguistic prejudice, and what are its types? Does linguistic prejudice is used in language? What is the relation between intolerance of speech and racial, social, religious, scientific … etc. discrimination? Understanding that relationship will help us to apprehend the general attitude of human beings better than before, which use those solid utterances as they have agreed on them like a collective agreement. The research will pose sufficient examples for each type and discuss each in depth and detail.